Lithostratigraphy of Baitadi area, far western Nepal - Mahara, AS (Journal of Nepal Geological Society, 2008)
Geological mapping of Baitadi and its surrounding area was carried out focusing on geological mapping and stratigraphic correlation. The metasedimentary rocks of the Baitadi area are classified into the Patan Group, Baitadi Group, and Tosh Group. The Baitadi Group contains carbonate rocks while the Patan Group is devoid of the carbonate rocks. The Tosh Group is basically a sedimentary rock sequence. The Patan and Baitadi groups are also distinct with each other by the characteristic features of coal bands, hematite beds, and pebbly sandstone of fluvial depositional environment. The Patan Group includes the Arubata, Bhandali, and Thum Formations, respectively from bottom to top. Similarly, the Baitadi Group is divided into the five formations namely: the Bhumeshor, Satbaj, and Dehimandu, Gadhi, and Julaghat Formations. The Tosh Group is divided into the Anarkholi Formation and Katal Formation. The Katal Formation and Anarkholi Formation are the younger rock units of the Tosh Group. The stratigraphic units of the area are correlated with the stratigraphic sequences of central and western Nepal. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.8